Gc-ms analysis of phytocomponents in the methanolic extract of propolis of stingless bee - SHASHIKALA.A, (International Journal of Pharma and Bio Sciences, 2016)
Propolis is a resinous Bee hive product and has been long used in folk medicine of different nations as early as 3000 BC. Stingless bees are indigenous pollinators of treasured herbal plants. Propolis of stingless bees is a natural, strongly adhesive mixture made of bee secretions and plant resins. Stingless bee Propolis exhibit a wide spectrum of pharmacological activities that vary depending on the geographical location, climate, generic type of bees and availability of botanical sources for the bees to forage. The present study was carried out to identify the phytocomponents present in the methanolic extract of the propolis of stingless bees reared and collected from Devanahalli, Bangalore, by GC-MS analysis. From the GC-MS results five compounds were identified as major constituents, they are Ethylhexanol, 1,1 dimethylethyl, 4,6 dimethyl, , Diethyl phthalate, 1,2 benezenedicarboxylic acid. These different active phytochemicals have been found to possess a wide range of Pharmacological activities, which may help in the protection against incurable diseases.